Safety and Effectiveness of Cell Therapy in Neurodegenerative Diseases: Take-Home Messages From a Pilot Feasibility Phase I Study of Progressive Supranuclear Palsy - Giordano, Rosaria; Canesi, Margherita; Isalberti, Maurizio; Marfia, Giovanni; Campanella, Rolando; Vincenti, Daniele; Cereda, Viviana; Ranghetti, Alessandra; Palmisano, Chiara; Isaias, Ioannis Ugo; Benti, Riccardo; Marotta, Giorgio; et al. (Frontiers in Neuroscience, 2021)
Mesenchymal stromal cells (MSCs) are multipotent cells with anti-inflammatory properties. Here we tested the safety of MSCs in patients with progressive supranuclear palsy (PSP) (ClinicalTrials.gov: NCT01824121; Eudract No. 2011-004051-39). Seven patients were treated. To improve the safety, protocol adjustments were made during the performance of the study. The objectives of our work were: 1) To assess the safety of MSCs. 2) To identify critical issues in cell therapies for neurodegenerative diseases. Autologous MSCs from the bone marrow (BM) of PSP patients were administered through the internal carotid arteries. One-year survival and number of severe adverse events were considered as safety endpoints. Clinical rating scales, neuropsychological assessments, gait and posture analysis, single-photon emission computed tomography (SPECT), positron emission tomography (PET) and brain magnetic resonance (BMR) were performed at different follow-up times. Peripheral blood levels of inflammatory cytokines were measured before and after cell infusion. Six of seven treated patients were living one year after cell infusion. Asymptomatic spotty lesions were observed at BMR after 24 hours in six of the seven treated patients. The last patient in the preliminary cohort (Case 5) exhibited transiently symptomatic BMR ischemic alterations. No severe adverse events were recorded in the last two treated patients. Interleukin (IL)-8 serum concentrations decreased in three patients (Case 2, 3 and 4). An adaptive study design, appropriate and up-to-date efficacy measures, adequate sample size estimation and, possibly, the use of acellular and/or allogeneic cell sources may help in performing phase II trials in the field.